Attenuation of satiety gut hormones increases appetitive behavior after curative esophagectomy for esophageal cancer. Issue 2 (5th February 2019) - Elliott, Jessie A; Docherty, Neil G; Haag, Jacqueline; Eckhardt, Hans-Georg; Ravi, Narayanasamy; Reynolds, John V; le Roux, Carel W
ABSTRACT: Background: Reduced appetite and weight loss are common after esophagectomy (ES), and this cohort demonstrates an exaggerated postprandial satiety gut hormone response. Satiety gut hormones modulate food reward, resulting in reduced energy intake. Objectives: This study aimed to determine the effect of satiety gut hormone modulation by measuring the effect of the somatostatin analog octreotide on appetitive behavior among patients after ES. Methods: In this randomized, double-blind, placebo-controlled crossover study, patients ≥1 y after ES and matched controls received either 1 mL 0.9% saline or 1 mL (100 μg) octreotide subcutaneously before completing a progressive ratio task. A measure of appetitive behavior, this task requires subjects to undertake progressively increasing amounts of work to obtain a sweet-fat reinforcer; the final completed increment (breakpoint) represents reinforcer reward value. Separate cohorts were studied in the fasted or 1-h postprandial states. Results: Thirty-six subjects (ES, n  = 18; matched controls, n  = 18) were studied. The ES subjects were 2.5 ± 0.3 y postoperation and had a weight loss of 14.6% ± 2.6% and elevated postprandial glucagon-like peptide 1 compared with controls (49.2 ± 13.4 compared with 20.2 ± 2.3 pM; P =  0.04). Octreotide did not alter the breakpoint among ES or control subjects when tested in a fasting condition (ES: 980 ± 371 compared with 1700 ± 584 clicks; P  = 0.16; controls: 1056 ± 274 compared with 1124 ± 273 clicks; P  = 0.81). When tested 1 h postprandially, octreotide was associated with an increased breakpoint compared with placebo among ES subjects (322 ± 143 compared with 246 ± 149 clicks; P  = 0.04) but not controls (248 ± 119 compared with 247 ± 120 clicks; P  = 0.97). Conclusions: Attenuation of the exaggerated postprandial satiety gut hormone response is associated with increased appetitive behavior toward a sweet-fat stimulus among patients post-ES. Suppression of satiety gut hormones may be a novel target to increase appetite, food intake, and body weight among patients after ES. This study was registered at clinicaltrials.gov as NCT02381249.